Examining internal migration effects on short versus long interbirth intervals in Cotonou, Benin Republic - Boladé Hamed Banougnin (BMC, 2019)
Abstract Background The literature on migration-fertility relationship uses various measures of fertility, such as fertility rates, actual fertility and family size preferences. This study introduces a different measure-interbirth intervals over women's reproductive years-to examine how internal migration is associated with short interbirth intervals (less than 24 months) and long interbirth intervals (greater than 60 months) in Cotonou, the largest city of Benin Republic. Methods The paper uses primary data on 2852 live births to 1659 women aged 15-49 years from the 2018 Fertility and Migration Survey in Cotonou. Competing-risks models were fitted for the analysis. Results Nineteen percent of live births were of short interbirth intervals and 16% were of long interbirth intervals. The prevalence of short interbirth intervals was higher among migrants who spent less than 5 years in Cotonou (29%) than among non-migrants (19%) and earlier migrants (18%). Non-migrants had the highest proportion of long interbirth intervals (19%). Within the first 5 years following the migration to Cotonou, migrants had higher subhazard ratio (SHR) of short interbirth intervals (SHR: 1.71, 95% CI: 1.33-2.21) and lower SHR of long interbirth intervals (SHR: 0.64, 95% CI: 0.47-0.87) than non-migrants. This association holds after controlling for socioeconomic characteristics-but with a slightly reduced gap between migrants who spent less than 5 years in Cotonou and non-migrants. Afterwards and irrespective of women's socioeconomic backgrounds, migrants who spent 5 or more years in Cotonou and non-migrants had similar risks of short and long interbirth intervals. Finally, from 5 years of stay in Cotonou, migrants for reasons other than school or job were less likely to experience short interbirth intervals (SHR: 0.65, 95% CI: 0.46-0.98 for migrants who spent 5-10 years in Cotonou, and SHR: 0.74, 95% CI: 0.54-1.02 for migrants who spent more than 10 years in Cotonou) than non-migrants. Conclusion Family planning programmes should mainly target migrants in the early years after their arrival in Cotonou. Moreover, non-migrants need to be sensitised on the adverse health outcomes of long interbirth intervals.